Sosialisasi Peningkatan Kesadaran Keamanan Digital dan Etika Bermedia Sosial bagi Kelompok PKK dan Siswa MTSN 3 Bekasi - Ratna Salkiawati; Afina Putri Dzulqiyana; Diah Ayu Lestari; Fauzi Muhtadi; Guntur Maulana Hidayah; Haikal Azizan; Handika Gita Prasojo; Herlan Ryuchi Christian; Hudan Aghil Muttaqin; Ihsan Ahmad Fauzan; Ihsan Rahmanda Albar; Ilyas Ahmat Dafianto; Imanuel Rodericus Parlindungan Tempo (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The rapid growth of digital technology has increased internet and social media usage in urban communities, including Mustika Jaya, Bekasi. However, this growth is not always accompanied by adequate digital literacy, particularly regarding digital security and social media ethics. This community service program aims to improve awareness and understanding of digital security and ethical behavior on social media among PKK women and junior high school students at MTsN 3 Bekasi. The program was conducted through socialization sessions, interactive discussions, demonstrations of digital security practices, and pre-test and post-test evaluations. The results indicate 25.7% increase in participants’ understanding of personal data protection, identification of online fraud, prevention of cyberbullying, and ethical communication on social media. This program contributes to strengthening digital literacy at the community level and supports the creation of a safer and more responsible digital environment.